A cultural genealogy of machismo: Mexico and the United States, cowboys and racism - Matthew C. Gutmann (Horizontes Antropológicos)
Abstract Men in Mexico have recently been characterized as uniformly macho by different anthropologists and other scholars, including those in the United States. This essay examines such social scientific categorization, and contrasts the uses and meanings of the terms macho and machismo in contemporary Mexico and the United States. What it means to be a macho-whether the macho is considered brutish, gallant, or cowardly-changes over time for various sectors of Mexican society in particular. Often the catchword machismo is employed in mutually exclusive ways today in Mexico, whereas in the United States it is generally assumed, in both popular and academic (official) writings, that machismo is an especially Mexican male characteristic. By capriciously glossing over significant differences among men based on class, generation, region, and ethnicity, among other factors, such generalizations have come to invent and then perpetuate sterile ideal types and racist stereotypes. The notable role of anthropologists of Latin America in the spread of these generalizations is detailed here. This paper draws on extensive and original ethnographic fieldwork in a colonia popular of Mexico City, on ethnohistorical materials concerning the cultural nationalist etymology of the word machismo, and on discussions with college youth in the United States concerning these terms and issues.